Specification for installation of gas fires, convector heaters, fire/back boilers and decorative fuel effect gas appliances. Gas fires, convector heaters, fire/back boilers and heating stoves (1st, 2nd and 3rd family gases) Part 1, (15th April 2001) - British Standards Institution,
No abstract available